Biosynthesis and evaluation of a novel highly water-soluble quercetin glycoside derivative - Cao, Jia-Nan; Wang, Wen-Hui; Qu, Yan-Jun; Xue, Guo-Li; Wei, Zhi-Yun; Liu, Jia-Qi; Han, Hui-Ying; Zhang, Sen; Song, Ping (Journal of asian natural products research, 2022)
Quercetin (1) was converted into quercetin 7-O-succinyl glucoside (2) by used Bacillus amyloliquefaciens FJ18 as a solvent-resistant whole-cell biocatalyst. The structure of the new compound was confirmed by LC-MS analysis and NMR spectroscopy. The water-solubility of this novel quercetin 7-O-succinyl glucoside (2) was approximately 1000 times higher than that of native quercetin (2). Quercetin (1) and quercetin 7-O-succinyl glucoside (2) exhibited significant DPPH scavenging capacity with IC 50 values of 23.55 and 36.05 µM, respectively. Both compounds showed moderate cytotoxic effects against the two human cancer cell lines (MCF-7 and HepG2) with IC 50 values ranging from 39.45-63.38 µM.